Local weather and body condition influence habitat use and movements on land of molting female southern elephant seals (Mirounga leonina). Issue 12 (20th May 2018) - Chaise, Laureline L.; Prinet, Iris; Toscani, Camille; Gallon, Susan L.; Paterson, William; McCafferty, Dominic J.; Théry, Marc; Ancel, André; Gilbert, Caroline
Abstract: Southern elephant seals ( Mirounga leonina ) are known to move and aggregate while molting, but little is known about their behavior on land during this time. In this study, 60 adult females were monitored (23 with GPS tags) during four molting seasons, between 2012 and 2016 at Kerguelen Archipelago, Indian Ocean. Population surveys were recorded each year ( N  = 230 daily counts), and habitat use was analyzed in relation to the stage of the molt and local weather. Based on stage of molt, habitat use, and movements on land, we classified the molt of elephant seals into three phases: (1) a "search phase" at the initial stage of molt when grass and wallow habitats were used and characterized by greater mean distances travelled on land per day compared with the two other phases; (2) a "resident phase": during initial and mid‐stage of molt when animals were found in grass and wallow habitats but with less distance moved on land; and (3) a "termination phase" at the final stage of molt where grass and beach habitats were occupied with no change in distances. Windchill and solar radiation influenced individual distances moved per day (mean 590 ± 237.0 m) at the mid‐ and final stage of molt such that animals travelled greater distances on days of low windchill or high solar radiation. Individual variation in distance moved and relative habitat use were also linked to body mass index (BMI) at arrival on the colony, as females with higher BMI moved less and preferred beach habitat. Moreover, the individual rate of molt increased with the use of wallows. Aggregation rate tended to be negatively correlated with distances moved. We therefore suggest that individuals face an energetic trade‐off while molting, balancing energy expenditure between movement and thermoregulation. Abstract : Based on stage of molt, habitat use, and movements on land, we classified the molt of elephant seals into three phases. Local weather variations influenced individual distances moved per day (mean 590 ± 237.0 m) during the molt. We therefore suggest that individuals face an energetic trade‐off while molting, balancing energy expenditure between movements, and thermoregulation.